Introducing Gunawangsa Manyar Hotel Through a Marketing Booklet - Evelina Larisa (Institute of Research and Community Outreach - Petra Christian University, 2018)
Gunawangsa Manyar Hotel is a three star hotel in the East of Surabaya. As a three star hotel, Gunawangsa Manyar Hotel also has competitors such as Swiss BelInn Manyar Hotel, Fave Hotel, Core Hotel, and Everbright Hotel. Compared to the competitors, Gunawangsa Hotel is not well known by many people. In introducing the hotel, they only use brochure and flyer for printed advertising. It means the tools they have are ineffective. Therefore, to introduce the hotel effectively, marketing booklet is the good solution for Gunawangsa Hotel since marketing booklet brings complete information needed by potential customers. The content of the booklet consists of company overview, product description, and contact information. In the product description, the USPs would be more emphasized. The USPs are obtained by the interview result with six guests of Gunawangsa Manyar Hotel.